UJI EKSPERIMENTAL MESIN PENDINGIN BERPENDINGIN UDARA, DENGAN MENGGUNAKAN REFRIGERAN R22 DAN REFRIGERAN R407C - Kevin Sanjaya; I Made Kartika; Harto Tanujaya (Jurnal Ilmiah Teknik Mesin POROS, 2014)
Abstract: Refrigerant R22 can cause ozone layer depletion so that required refrigerant substitute for R22. Refrigerant R407C is one of the refrigerant substitute for R22. Research of refrigerant in the cooling engine with air-cooled condenser is done by experimental methods. This research was conducted using refrigerants R22 and refrigerant R407C with a flow rate of 20 L /h, 40 L/h, 80 L/h and 120 L/h. Test data processing include the calculation of refrigeration capacity, compressor power and COP values. COP or Coefficient Of Performance shows the efficiency of the refrigerant. The best COP values are in the refrigerant flow rate of 40 L/h, with R22 COP value of 5.818 and R407C COP value of 4.875.